2019
DOI: 10.1371/journal.pone.0221890
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of carnivore carcasses by vertebrate scavengers enables colonization by a diverse community of carrion insects

Abstract: Carrion resources sustain a complex and diverse community of both vertebrate and invertebrate scavengers, either obligate or facultative. However, although carrion ecology has received increasing scientific attention in recent years, our understanding of carrion partitioning in natural conditions is severely limited as most studies are restricted either to the vertebrate or the insect scavenger communities. Moreover, carnivore carcasses have been traditionally neglected as study model. Here, we provide the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 79 publications
3
37
0
Order By: Relevance
“…However, the bait site situation in the BFNP with regular and year-round carrion supply guarantees a localized increased carrion volume over time despite the vertebrate scavenger visitors. Consequently, besides the above-discussed facilitation hypotheses, a highly diverse successional insect community could be a result of the total carrion volume, commensurate with the results of Moleón [ 65 ] and Muñoz-Lozano [ 66 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…However, the bait site situation in the BFNP with regular and year-round carrion supply guarantees a localized increased carrion volume over time despite the vertebrate scavenger visitors. Consequently, besides the above-discussed facilitation hypotheses, a highly diverse successional insect community could be a result of the total carrion volume, commensurate with the results of Moleón [ 65 ] and Muñoz-Lozano [ 66 ].…”
Section: Discussionsupporting
confidence: 75%
“…Regarding carrion volume, Moleón [ 65 ] suggested that increased carrion biomass resulting from vertebrate scavenger reductions at carnivore carcasses enables a successional insect community of the remains. This was confirmed by a carnivore carcass avoidance-study of Muñoz-Lozano [ 66 ], showing a well-structured and diverse insect community consisting of necrophages, omnivores, and necrophilous predators and parasitoids. In contrast to the studies of Moleón [ 65 ] and Muñoz-Lozano [ 66 ], no carnivore carcasses were exposed at our fixed locations, and access by vertebrate scavengers, such as red foxes, pine martens, or Eurasian lynx, to the exposed roe and red deer carcasses took place [ 21 ].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In fact, some studies suggest that vertebrate scavengers actively avoid consuming carnivore carcasses, or at least conspecifics, as scavenging these resources may be associated with a greater likelihood of exposure to infectious diseases [ 35 ]. This avoidance strategy by vertebrate scavengers has also been shown to facilitate greater opportunities for invertebrate scavengers to exploit carnivore carcasses [ 36 ], which likely explains the carnivore bias in our blow flies collected in the national parks.…”
Section: Discussionmentioning
confidence: 99%
“…2) might have consequences for the toads themselves. Necrophagous invertebrates are an important driver of carrion decomposition, and increase in abundance if carcasses are left unscavenged by vertebrates (Munoz‐Lozano et al 2019). More broadly, cane toads key in on resource patches that offer abundant prey (González‐Bernal et al 2013, Feit et al 2015).…”
Section: Discussionmentioning
confidence: 99%